Observations From a Mouse Model of Forebrain Voa1 Knockout: Focus on Hippocampal Structure and Function - Ma, Ke; Bin, Na-Ryum; Shi, Shan; Harada, Hidekiyo; Wada, Yoh; Wada, Ge-Hong-Sun; Monnier, Philippe P.; Sugita, Shuzo; Zhang, Liang (Frontiers in Cellular Neuroscience, 2019)
Voa protein is a subunit of V-ATPase proton pump which is essential to acidify intracellular organelles including synaptic vesicles. Voa1 is one of the four isoforms of Voa family with strong expression in neurons. To examine the role of Voa1 protein in mammalian brain neurons, we generated conditional Voa1 knockout mice in which Voa1 was selectively deleted from forebrain pyramidal neurons. We examined the Voa1 knockout mice of ages 5-6 months to assess persistent effects of Voa1 deletion. The Voa1 knockout mice exhibited poor performance in the Morris water maze test compared to control mice. In addition, synaptic field potentials of the hippocampal CA1 were greatly diminished in the Voa1 knockout mice when examined in brain slices in vitro. Furthermore, the Voa1 knockout mice presented severe degeneration of dorsal hippocampal CA1 neurons while CA3 neurons were largely preserved. The CA1 neurodegeneration was associated with general brain atrophy as indicated by an overall decrease in hemispheric areas. Despite the CA1 degeneration and dysfunction, the Voa1 knockout mice exhibited hippocampal CA3 electroencephalographic spikes and non-convulsive discharges. These hippocampal spikes were suppressed by single intra-peritoneal injection of diazepam which is a benzodiazepine GABAa receptor enhancer. Together these results suggest that Voa1 related activities are essential for survival of the targeted neurons in the dorsal hippocampal CA1 as well as other forebrain areas. We postulate that the Voa1 knockout mice may serve as a valuable model for further investigation of V-ATPase dysfunction related neuronal degeneration and functional abnormalities in forebrain areas particularly the hippocampus.